Research and response strategies on the impact of goaf collapse on overhead transmission lines - Siqing Xu; Xiaokai Meng; Shuai Wang; Zhumao Lu; Wen Shang (AIP Advances)
This article examines the impact of goaf collapse on overhead transmission lines, delving into various aspects such as foundation deformation, tower foundation and simulation calculation errors, tower deformation, and the effects at hanging points. Through a detailed analysis of surface deformation, the study reveals the laws and characteristics of surface deformation in goaf areas and proposes corresponding coping strategies. At the same time, it emphasizes the importance of precise monitoring, structural optimization design, long-term monitoring and maintenance, and emergency plan formulation to ensure the stable operation of the power system.